PENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR PKN MELALUI METODE PEMBERIAN TUGAS PADA SISWA KELAS IV SDN 3 PENENGAHAN BANDAR LAMPUNG - Dewi, Maria (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
This research was conducted with the aim of describing the increase in civics learning activity and achievement through the method of giving assignments to fourth grade students of SDN 3 Penengah, Kedaton District, Bandar Lampung. The problem in this study is the low activity and achievement of Civics learning in grade IV students. The research objective was to increase civics learning activities and achievement in grade IV SDN 3 Penengah Bandar Lampung. This research is a Classroom Action Research (CAR) conducted by using 3 cycles. Collecting data in this study using observation and test guidelines. Data were analyzed descriptively and quantitatively. The results of the data analysis showed that there was an increase in student learning activities in cycle I was obtained 23%, cycle II was obtained 43%, and cycle III was obtained 86%. The increase in student activity in the first cycle increased 23%, and the third cycle increased 44%. The learning achievement of students in the first cycle increased 20%, the second cycle obtained 47%, and the third cycle obtained 87%. The increase in student activity in the first cycle increased 20%, the second cycle was 43%, and the third cycle increased 44%, it was 87%. The conclusion of the research is that learning using the assignment method can increase Civics learning activity and achievement in grade IV SDN 3 Penengah.